Dapatkah Literasi Digital Muslim Berbasi Etika, Kecerdasan Buatan (AI), dan Media Islami Membentuk Karakter di era Digital? - Aghnia Nur Muthmainah; Afifah Nurul Latifah; Raden Muhammad Hilmi Maulana (Jurnal Budi Pekerti Agama Islam, 2026)
The importance of digital literacy in shaping Muslim identity in the digital age, trough Islamic values and technological developments. The increasingly rapid development of digital media has transformed the way people communicate, learn, and buid self-image in society. This condition encourages the younger generation, especially Muslim students like us, to understand ethics, digital responsibility, and critical awareness in using technology. This study aims to analyze the role of digital literacy, Islamic media ethics, artificial intelligence (AI), digital privacy, and Islamic personal branding in developing responsible digital behavior. The research method used is a qualitative descriptive approach throgh a literature review of journal, books, and scientific publications related digital literacy functions not only on technical skills, and the application of islamic values in interactions in the digital world. Furthermore the presence of AI and social media trend presents both opportunities and challenges for Muslims in maintanining ethics, privacy, and self-identity. We also imply that strengthening Islamic digital literacy is essential to creating a generation that is adaptive, ethical, and wise in facing technological transformations in the modern era.